Good Practice in Strengthening Integrity and Transparency in Organizations: A Case Study of the Department of Provincial Administration, Ministry of Interior - Nitthat-ek, Siriruk (King Prajadhipok’s Institute Journal, 2025)
This research, Good Practice in Strengthening Integrity and Transparency in Organizations: A Case Study of the Department of Provincial Administration, Ministry of Interior, has three main objectives. First, it examines the Department of Provincial Administration’s (DOPA) efforts to foster integrity and transparency under the Integrity and Transparency Assessment (ITA). Second, it analyzes the key success factors and operational challenges DOPA has encountered in adopting the ITA. Third, it proposes recommendations for other governmental organizations to use the ITA as a tool for improving public services. This study employs a document-based approach combined with in-depth interviews with eleven stakeholders. The findings indicate that the Thai government introduced the ITA in 2013 to enhance public sector integrity. In 2019, the ITA transitioned to an online platform, leading to a temporary decline in DOPA’s score. In response, DOPA implemented organizational reforms under the Bumbudtook Bumrungsook vision, integrating ITA evaluation criteria into its anti-corruption strategy. Through this plan, DOPA is committed to promoting a policy of honesty, enhancing transparency through IT initiatives, and implementing various related projects. DOPA has achieved key successes, including the establishment of an Anti-Corruption Operational Center and improvements in its monitoring and evaluation processes. The department adopts an incremental approach to goal-setting, with executives prioritizing clear goal definitions. In terms of organizational culture, DOPA fosters a positive environment for its members. Occasionally, they demonstrate anti-corruption behavior in passive ways. To support ITA implementation, DOPA sets strategic goals, allocates resources, encourages executives to integrate ITA criteria into organizational programs, employs both incentive-based ('carrot and stick') strategies, and conducts annual lessons-learned meetings to drive ITA evaluation. Lastly, the lessons learned from DOPA might not be universally applicable to other governmental organizations due to various constraints. However, as a good practice, DOPA demonstrates significant lessons as a 'role model framework' for other organizations on how to implement functional and concrete policies. Furthermore, DOPA is committed to improving public services in the long term by integrating good governance principles with ITA criteria. Additionally, it aims to instill ITA knowledge and good governance values among its officers to support the organization's sustainable development. All lessons learned are important for other organizations in practical terms. This research suggests that the department emphasize leadership in specific areas related to this responsibility and strengthen cooperation between internal officers, external stakeholders’ networks, and service recipients. Additionally, citizen engagement should be developed as a key instrument for service recipients.